FACILITATION SESSION ON ASSESSING THE BORROWER’S CREDITWORTHINESS (ONLINE) - Lakhtionova, Liudmyla; Tkachenko, Viktoriia; Kavunov, Oleksandr (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The features of lending in Ukraine under martial law conditions are reflected. The preparation for the facilitation session on assessing the creditworthiness of a potential borrower was considered. Proposals were made to prepare the thematic discussion and improve the quality of its conduct. Discussed issues on the method of analyzing the counterparty’s creditworthiness are highlighted, the solution of which will contribute to reaching a consensus by the participants in credit processes.